2018
DOI: 10.1073/pnas.1719885115
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary emergence of the rac3b / rfng / sgca regulatory cluster refined mechanisms for hindbrain boundaries formation

Abstract: Developmental programs often rely on parallel morphogenetic mechanisms that guarantee precise tissue architecture. While redundancy constitutes an obvious selective advantage, little is known on how novel morphogenetic mechanisms emerge during evolution. In zebrafish, rhombomeric boundaries behave as an elastic barrier, preventing cell intermingling between adjacent compartments. Here, we identify the fundamental role of the small-GTPase Rac3b in actomyosin cable assembly at hindbrain boundaries. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 81 publications
2
54
0
Order By: Relevance
“…At this stage, the hindbrain boundary cells appear at the interface between rhombomeres ( Figure 1A-D) and expand all along the dorsoventral domain of the hindbrain (Cheng et al, 2004). They express a specific set of genes (Letelier et al, 2018), and remarkably, no proneural genes. The latter are expressed in zones that flank rhombomere boundaries in which they drive neurogenesis (Nikolaou et al, 2009).…”
Section: Hindbrain Boundary Cells Display Yap/taz-tead Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…At this stage, the hindbrain boundary cells appear at the interface between rhombomeres ( Figure 1A-D) and expand all along the dorsoventral domain of the hindbrain (Cheng et al, 2004). They express a specific set of genes (Letelier et al, 2018), and remarkably, no proneural genes. The latter are expressed in zones that flank rhombomere boundaries in which they drive neurogenesis (Nikolaou et al, 2009).…”
Section: Hindbrain Boundary Cells Display Yap/taz-tead Activitymentioning
confidence: 99%
“…Functionally, it was shown that these boundary cells act as an elastic mesh to prevent cell mixing between adjacent rhombomeres. This is due to the assembly of actomyosin cable-like structures in the apical side of these cells that generate tension within this cell population (Calzolari et al, 2014;Letelier et al, 2018). Given the compelling evidence for the relevance of YAP and TAZ as downstream mediators of mechanical cues, we investigated the role of Yap/Taz-TEAD activity within boundary cells as putative sensors of changes in cell and tissue architecture.…”
Section: Hindbrain Boundary Cells Display Yap/taz-tead Activitymentioning
confidence: 99%
See 3 more Smart Citations